The development of process-based information systems: methodological requirements - Pereira, José Luís (2016)
At the present time several issues are dramatically challenging the way we build and maintain information systems. On the one hand, owing to the extremely competitive conditions and dynamics of the business environment, it is vital for organisations to be able to develop and modify their information systems as quickly as possible, in order to succeed or even to keep in business. On the other hand, new technological developments have recently brought to the information systems infrastructure a set of new technologies with enormous potential to improve the way information systems support organisations. Collaborative technologies and, in particular, workflow, are notorious examples. In this paper, we propose a new information systems framework (Process-based Information Systems), which is able to provide organisations with the means to respond timely and adequately to the opportunities and threats of the business environment. Regarding this framework we try to identify the limitations of conventional Information Systems Development methodologies and, therefore, propose a set of new methodological requirements.